2015
DOI: 10.1021/ja512022r
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Concise Synthesis of Ouabagenin and Hydroxylated Corticosteroid Analogues

Abstract: The natural product ouabagenin is a complex cardiotonic steroid with a highly oxygenated skeleton. This full account describes the development of a concise synthesis of ouabagenin, including the evolution of synthetic strategy to access hydroxylation at the C19 position of a steroid skeleton. In addition, approaches to install the requisite butenolide moiety at the C17 position are discussed. Lastly, methodology developed in this synthesis has been applied in the generation of novel analogues of corticosteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 81 publications
1
78
0
2
Order By: Relevance
“…207,208 Baran’s team found that Mukaiyama’s hydration 105 procedure could install the C-14 tertiary alcohol 94 from the trisubstituted alkene 93 in 86% yield and 8:1 diastereoselectivity. Use of dioxane as solvent improved the diastereoselectivity of the nascent alcohol.…”
Section: C-o Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…207,208 Baran’s team found that Mukaiyama’s hydration 105 procedure could install the C-14 tertiary alcohol 94 from the trisubstituted alkene 93 in 86% yield and 8:1 diastereoselectivity. Use of dioxane as solvent improved the diastereoselectivity of the nascent alcohol.…”
Section: C-o Bondsmentioning
confidence: 99%
“…Consequently, we do not discuss these numerous reactions further except to state that a number of groups have found uses for this reaction in complex molecule and natural product syntheses. 207,208,386,387,388,389,390,391 …”
Section: Hydrogenation and Isomerizationmentioning
confidence: 99%
“…Subsequently, the Baran group successfully implemented this strategy in the synthesis of polyoxygenated cardiotonic steroid ouabagenin from progesterone . As progesterone does not contain the β‐C14 hydroxyl group, Baran and co‐workers installed this moiety using Δ 14 ‐alkene‐containing intermediate 66 (Scheme ).…”
Section: Syntheses Enabled By Transition Metal Catalysismentioning
confidence: 99%
“…Shortly afterward, they published a full account describing the synthesis of 2 and the approach toward C-19-hydroxylated corticosteroid analogs [36,37]. Shortly afterward, they published a full account describing the synthesis of 2 and the approach toward C-19-hydroxylated corticosteroid analogs [36,37].…”
Section: Ouabageninmentioning
confidence: 99%